LGBT Rights in Southeast Asia: One Step Forward, Two Steps Back? - Wilkinson, C.; Gerber, P.; Offord, Baden; Langlois, A. (2017)
Although in recent years many leading international actors, including the UN and European Union, have endorsed the idea that “LGBT [lesbian, gay, bisexual and transgender] rights are human rights and human rights are LGBT rights” (Clinton, 2011), at the regional and national levels support is still far from guaranteed. The result is that while globally there has been significant progress in recognising the rights of LGBT people, at times assisted by and resulting in cultural transformation, there has also been an accompanying rise in both popular, religious and political homophobia in many states. These conflicting and frequently highly contradictory dynamics are particularly evident in Southeast Asia, where some great leaps forward in protecting the rights of LGBT people have occurred in parallel with substantial setbacks. For example, in late 2014, a Malaysian Appeals Court ruled that a ban on crossdressing was unconstitutional, while a Singapore Court held that a law criminalising consensual same-sex conduct between men was constitutional. This paper explores the debates and trajectories of LGBT rights in Southeast Asia from four different perspectives in order to assess not only the overall state of LGBT rights in the region, but also to consider how further progress towards meaningful protection of LGBT rights can be achieved.